Digital Platform Liability for Economic Crimes in Online Marketplaces - Dinda Aprilia; Tippawan Lertatthakornkit; Chibueze Callistus Duru; Muhammad Arbani (Jurnal Justice Dialectical, 2026)
The rapid growth of digital marketplaces has transformed commercial activities and expanded public access to goods and services. At the same time, this development has created greater opportunities for economic crimes, including online fraud, money laundering, identity theft, illegal trade, and misuse of personal data. These problems raise important legal questions concerning the responsibility of digital platforms that manage commercial transactions and control marketplace activities. This study analyzes the legal liability of digital platforms for economic crimes within marketplace ecosystems and develops an appropriate model of platform accountability for Indonesia by drawing lessons from Singapore. The study applies normative legal research through statutory, conceptual, and comparative approaches. The findings reveal three major problems. First, Indonesian law regulates digital platform responsibility through fragmented provisions that do not clearly define the scope of platform liability for economic crimes committed by third parties. Second, the existing legal framework does not impose adequate obligations on platforms to conduct due diligence, identify transaction risks, prevent unlawful activities, and maintain effective internal governance. Third, the comparison with Singapore demonstrates the importance of preventive obligations, effective risk assessment, transparent governance, and proportionate responsibility in strengthening platform accountability. This study concludes that Indonesia should establish a risk-based accountability model that requires digital platforms to actively prevent foreseeable economic crimes while maintaining proportionate liability according to their authority, knowledge, control, and involvement in marketplace activities.